Exploring the Medication Patterns of Traditional Chinese Medicine in the Treatment of Chronic Cholecystitis Based on the Ancient and Modern Medical Cases Cloud Platform - Pu, Jinjin; Jiang, Linlin; Dong, Yonghong (Journal of Contemporary Medical Practice, 2025)
Objective: As a country with a high prevalence of hepatobiliary diseases, chronic cholecystitis is one of the most common hepatobiliary disorders in China. Studies [1] have shown that early surgical intervention yields better outcomes after a confirmed diagnosis of chronic cholecystitis. However, due to the high risks of surgery, frequent postoperative complications, and stringent timing requirements, integrated traditional Chinese and Western medicine conservative therapy has emerged as a viable alternative. Therefore, this study utilizes the Ancient and Modern Medical Case Cloud Platform to investigate the medication patterns of traditional Chinese medicine (TCM) in treating chronic cholecystitis, aiming to alleviate clinical symptoms through TCM therapies. Methods: Literature and medical case reports related to TCM treatment of chronic cholecystitis were retrieved from the CNKI, VIP, and Wanfang databases. After data screening and standardization, a standardized database for chronic cholecystitis was established. Statistical analysis, hierarchical clustering analysis, and association analysis were applied, followed by visual representation to explore medication patterns and summarize clinical experience. Results: A total of 197 prescriptions were included, involving 209 herbal medicines. The core medications were Bupleurum (Chaihu), White Peony Root (Baishao), Turmeric (Yujin), Lysimachia (Jinqiancao), Scutellaria baicalensis (Huangqin), and Licorice (Gancao). The predominant properties were slightly cold and bitter, primarily targeting the liver and spleen meridians. Conclusion: TCM treatment for chronic cholecystitis primarily employs herbs to soothe the liver and relieve stagnation, clear heat and detoxify, while also incorporating agents to promote bile flow, reduce jaundice, and uplift yang qi.